Fundamental frameworks for questionnaire-based paediatric vision screening development / Ai Hong Chen and Nurul Farhana Abu Bakar - Ai Hong, Chen; Abu Bakar, Nurul Farhana (Division of Research, Industrial Linkages and Alumni, UiTM Cawangan Melaka, 2023)
This paper explores the potential of using questionnaires as vision screening apparatus for the paediatric population. A systematic review was executed to scrutinise the influencing factors of the existing vision screening. Our survey and experiment unveiled the scarcity of operational information on vision screening implementation. The characteristic of the current questionnaire items was analysed. Our findings are consolidated into five fundamental frameworks. The first framework reveals the practising pattern and historical evolution of vision screening. The second framework exhibits challenges, coverage and variation in the implementation. The third framework displays the potential fabric of operation alternatives in vision screening. The fourth framework illustrates the establishment encounters. The fifth framework defines the characteristics of visionrelated questionnaires. Two coalesced frameworks conclude the holistic questionnaire concept in paediatric vision screening.